Drying Characteristics and Mathematical Model for Heat Pump Low Temperature Drying of Tenebrio Molitor - Xue Yameng; Li Baoguo (Zhileng xuebao)
In order to study the heat pump low temperature drying characteristics of biological material, the tenebrio molitors, as drying materials, was dried with heat pump under the conditions of different air temperatures, air velocities and blanching time. The drying characteristics of tenebrio molitors were studied and the drying processing was correlated by typical drying model. The results show that the drying process of tenebrio molitor could be divided into three stages, i.e., acceleration drying period, constant-rate drying period and falling rate drying period. The drying time can be shortened with the increasing of air temperature, air velocity and blanching time. An optimum model was chosen based on their coefficients of determination R2，root mean square error(RMSE) and sum of squared error(SSE). It is shonw that the Midilli model was superior to others in describing the drying curves of tenebrio molitors, and the R2, RMSE and SEE value respectively were 0.99971, 0.00559 and 0.00104. The experimental data of MR was in agreement with the predicted results of Mildilli model.